A Comparative Analysis of the Labor Market Performance of University-Educated Immigrants in Australia, Canada, and the United States: Does Policy Matter? - Clarke, Andrew; Ferrer, Ana; Skuterud, Mikal (Journal of Labor Economics, 2019)
We examine data from Australia, Canada, and the United States to assess the potential for immigrant screening policies to influence the labor market performance of skilled immigrants. Our estimates point to improvements in employment rates and weekly earnings of male university-educated immigrants in all three countries concomitant with policy reforms. Nonetheless, the gains are modest in comparison to a substantial and persistent performance advantage of US skilled immigrants. Given that there is increasingly little to distinguish the screening policies of these countries, we interpret the US advantage as primarily reflecting the relative positive self-selectivity of US immigrants.